Risk Reduction, Risk Sharing and Moral Hazard: A Vaccination Metaphor - Frank Vandenbroucke (Intereconomics, 2017)
This paper focuses on unemployment insurance; it sketches the rationale for a degree of centralisation that would create a lean insurance union, addressing the risk of large economic shocks.
Keywords: 330